2008
DOI: 10.1116/1.3010735
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of the nanoimprint mold using inorganic electron beam resist with post exposure bake

Abstract: Articles you may be interested inLarge-diameter roll mold fabrication method using a small-diameter quartz roll mold and UV nanoimprint lithography J. Vac. Sci. Technol. B 29, 06FC08 (2011); 10.1116/1.3657524Fabrication of a seamless roll mold using inorganic electron beam resist with postexposure bake J. Vac. Sci. Technol. B 29, 06FC06 (2011); 10.1116/1.3656052Fabrication of nanodot array molds by using an inorganic electron-beam resist and a postexposure bake Time-dependent exposure dose of hydrogen silsesqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They showed that this enhanced thermal treatment breaks down a significant portion of the photoactive materials, which allows to decrease the relationship between the development rate and the exposure dose. Mortelmans et al 19 and Unno et al 20 investigated the influence of a PEB on the dose-response behavior of PMMA and NIMO-P0701 resist, respectively, using electron beam lithography. They obtained a decrease in the depth of development if a PEB is carried out at high temperatures and for a longer time for a given dose.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that this enhanced thermal treatment breaks down a significant portion of the photoactive materials, which allows to decrease the relationship between the development rate and the exposure dose. Mortelmans et al 19 and Unno et al 20 investigated the influence of a PEB on the dose-response behavior of PMMA and NIMO-P0701 resist, respectively, using electron beam lithography. They obtained a decrease in the depth of development if a PEB is carried out at high temperatures and for a longer time for a given dose.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the contrast curve for SOG material was improved. 13 Moreover, the surface of the obtained pattern was smooth. Therefore, the pull-up speed is very important in the formation of the resist layer on a roll substrate using the dipping method.…”
Section: Experimental Setup and Methodologymentioning
confidence: 97%
“…12 In this study, we employed a high-resolution inorganic EB resist and the pattern shrink effect via postexposure bake (PEB). 13 Using this technique, the contrast of spin-on-glass (SOG) material was drastically improved and could be controlled by the PEB temperature. Moreover, because PEB is a thermal process, it is not limited by machine accuracy, such as during vibration of the a) Research Fellow of the Japan Society for the Promotion of Science.…”
Section: Introductionmentioning
confidence: 99%
“…By using the master CGH pattern mold, an inverted mold was duplicated by UV-NIL onto a polyester film substrate (Cosmoshine A4300; Toyobo Co., Osaka). In this case, we used PAK-01-CL (Toyo Gosei Co., Tokyo) as the UV-curable resin, and the fabricated mold was processed directly by UV-NIL, thus eliminating the etching processes [13]. Finally, the CGH pattern was transferred onto a silicon wafer by NIL with the inverted mold.…”
Section: Experimental Methodsmentioning
confidence: 99%